Prevalence and factors associated with late presentation for HIV care among adult men at a large HIV clinic in Eastern Uganda: A cross-sectional study - Sherifah Nabikande; Juliana Namutundu; Joanita Nangendo; Steven Ndugwa Kabwama; Anne Ruhweza Katahoire (Journal of Interventional Epidemiology and Public Health)
Introduction: In Uganda, men diagnosed with HIV still present late for care. Understanding the drivers of late presentation among men is a critical step towards achieving the full potential of HIV treatment scale-up. This study aimed to determine the prevalence and factors associated with late presentation for HIV care among adult men in Jinja District, Eastern Uganda.